2012
DOI: 10.1128/jcm.00607-11
|View full text |Cite
|
Sign up to set email alerts
|

First Worldwide Proficiency Study on Variable-Number Tandem-Repeat Typing of Mycobacterium tuberculosis Complex Strains

Abstract: f Although variable-number tandem-repeat (VNTR) typing has gained recognition as the new standard for the DNA fingerprinting of Mycobacterium tuberculosis complex (MTBC) isolates, external quality control programs have not yet been developed. Therefore, we organized the first multicenter proficiency study on 24-locus VNTR typing. Sets of 30 DNAs of MTBC strains, including 10 duplicate DNA samples, were distributed among 37 participating laboratories in 30 different countries worldwide. Twenty-four laboratories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 31 publications
0
47
0
1
Order By: Relevance
“…A few studies have investigated the intra-and interlaboratory reliability of MIRU-VNTR typing. In particular, they confirmed that manual methods can present discrepancies and allele-calling failures (9). These factors hinder the wider implementation of this method.…”
mentioning
confidence: 59%
“…A few studies have investigated the intra-and interlaboratory reliability of MIRU-VNTR typing. In particular, they confirmed that manual methods can present discrepancies and allele-calling failures (9). These factors hinder the wider implementation of this method.…”
mentioning
confidence: 59%
“…The introduction of this genotyping method replaced IS6110-RFLP as the gold standard and allowed VNTR patterns to be compared in international databases. Because of the ease of use and the improved performance, VNTR typing has been integrated in TB control programs on an international scale in the United States, Europe, and other parts of the world [30,44]. A global epidemiological database is available that has led to insights into the geographical distribution and evolution of M. tuberculosis [26,44].…”
Section: Vntr Typingmentioning
confidence: 99%
“…The determination of the tandem repeat sizes can be performed in an agarose gel-based electrophoresis method or on DNA sequencing machines. Moreover, the results are expressed as numerical codes and are therefore very easy to compare and exchange [44,52]. Among different sets of MIRU-VNTR loci described for typing M. tuberculosis isolates, a new international standard typing method system based on 24 loci was proposed in 2006, by a group of international institutions [17].…”
Section: Vntr Typingmentioning
confidence: 99%
“…The first round of worldwide proficiency testing initiated by our laboratory within the framework of an ECDC project revealed that both the intralaboratory and interlaboratory reproducibilities are to be improved in a number of laboratories, indicating the need for careful implementation (20). Moreover, new patient cluster identification numbers and compositions resulting from the discordances with RFLP typing introduced a major challenge for the TB units of the Municipal Health Services.…”
Section: Figmentioning
confidence: 99%